Environnement et éducation : analyse d’une stratégie d’introduction d’une éducation à l’environnement en Algérie - Ahmed Ghouati (VertigO)
The introduction of the Education for the environment in Algeria is connected with an institutional education strategy for the lasting environment and development (Education for the Environment and Sustainable Development, EEDD). Within the framework of this strategy, human and material means were mobilized. However, this introduction did neither represent a moment to reconsider the polytechnical orientation of the school nor to rearrange the utilization of time and to distribute the contents of the textbooks better. For example, much before the establishment of the national strategy of EEDD, the incorporation of a subject called "Environment studies" at the beginning of the years of 2000 has not included significantly the utilization of time. We have also analyzed sensible textbooks translating the objectives of the EEDD such as defined in the agreement signed in 2002 between the ministries of environment and national education for the introduction of the Education for the environment. The analysis has utilized four catagories of items, namely "Nature, Ecology, Life", "Health, Culture, Family, Education", "Pollution, Threats", "Measures of protection and reorganization". Quantitatively, the obtained results indicate a significant change with regard to the previous textbooks examined by Remki, Clément, and Khemmar (2000). Nevertheless, the subjects connected with the environment are not always problematized qualitatively. Furthermore, the textbooks are divided into two large categories as far as the question of problematization is concerned : the normative and prescriptive textbooks and the descriptive and explicative textbooks. In the first type, we find the textbooks of religious and civic education and in the second one, the textbooks of scientific/technological education and of geography. The second category offers better pedagogical possibilities, particularly for the implication of the teachers and pupils/students.